Sintomas externos (morfológicos) e internos (anatômicos), observados em folhas de goiabeira (Psidium guajava L.), de plantas cultivadas em solução nutritiva com carência dos macronutrientes - Accorsi, W. R.; Haag, H. P.; Mello, F. A. F. de; Brasil Sobrinho, M. O. C. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1960)
The present work was carried out in order to study: (1) The symptoms of deficiency of macronutrients (N, P, K, Ca, Mg, S) in guava (Psidium guajava L.). (2) The modifications induced by those treatments in the histological make up of the leaves. Young guava plants were grown in nutrient solution two treatments being used, namely: complete solution (HOAGLAND and ARNON, 1950), deficient solution, in which a given element was ommitted. The main conclusions can be summaryzed as follows. a) Symptoms Clear cut symptoms of malnutrition were observed in the treatments: -N, -P, -Ca, -K, -Mg, and -S. The signal - stared respectively for deficient level. b) Histological effects Usually the characteristics of the chloroplasts were affected: loss of the green and coalescence into irregular bodies.